Video for peer feedback and reflection: embedding mainstream engagement into learning and teaching practice - Lindsay Jordan (Association for Learning Technology, 2012)
This paper discusses the benefits and challenges of video as a tool for supporting and enhancing peer feedback and reflection. The analysis draws on key arguments from relevant literature in combination with the author's own experiences of producing and using video recordings of peer feedback sessions, presentations and personal reflections, and on learners’ experiences of the same, gathered through feedback interviews. A number of potential benefits are presented, including the exposure of additional and alternative perspectives, the assistance of focus and recall, increased impact and greater flexibility of learning. Several challenges are also explored, such as privacy of and access to recordings, participant anxiety, technical challenges and access to hardware. Strategies are offered for capitalising on the benefits while addressing the challenges. It is concluded that thoughtful use of video in the curriculum can augment the existing multiple benefits of reflection, enquiry and/or evaluation. In the specific context of teacher education, it is argued that the embedded use of technologies such as video in professional development courses can help to develop the digital literacy of teaching staff.